2008
DOI: 10.2334/josnusd.50.15
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence and distribution of odontogenic cysts in Sicily: 1986 - 2005

Abstract: The objective of this study was to assess the prevalence of odontogenic cysts (OCs) in Sicily and evaluate their distribution during a 20-year period. A cross-sectional retrospective study was carried out in 1,310 cysts of the jaw diagnosed in 12,197 individuals, who consecutively attended the Odontostomatologic Clinic of Palermo from 1986 to 2005. 1,273 cysts were classified as odontogenic, whereas only 37 were nonodontogenic. In the former group, the most frequent lesions were radicular cysts (84.5%), follow… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

47
85
7
16

Year Published

2010
2010
2024
2024

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 91 publications
(157 citation statements)
references
References 9 publications
47
85
7
16
Order By: Relevance
“…Whether this peak incidence of dentigerous cysts in older age groups is a particular characteristic of this European population is still a matter of discussion. Odontogenic keratocysts have been described as the third most common type of OC, with frequencies ranging from 1.3% to 21.5% (1,3,4,5,7,8,13), in agreement with the present findings. Most cases of odontogenic keratocysts are diagnosed in men between the second and third decades of life (2-4, 5,7,8).…”
Section: Discussionsupporting
confidence: 82%
See 3 more Smart Citations
“…Whether this peak incidence of dentigerous cysts in older age groups is a particular characteristic of this European population is still a matter of discussion. Odontogenic keratocysts have been described as the third most common type of OC, with frequencies ranging from 1.3% to 21.5% (1,3,4,5,7,8,13), in agreement with the present findings. Most cases of odontogenic keratocysts are diagnosed in men between the second and third decades of life (2-4, 5,7,8).…”
Section: Discussionsupporting
confidence: 82%
“…The 1.019 cases of OCs identified in the present study accounted for 11.0% of all specimens stored in the archives of the Oral Pathology Service at UFRN. Similar results have been reported in previous studies invol-ving populations from Brazil (3), Chile (4), Sicilia (13), and the United Kingdom (2). Studies involving Mexican populations have shown lower frequencies of OCs ranging from 7.8% to 8.4% (6,7).…”
Section: Discussionsupporting
confidence: 79%
See 2 more Smart Citations
“…Estudios internacionales han reportado una prevalencia general dentro de las lesiones del territorio maxilofacial de un 10,4%, siendo el quiste radicular el mas prevalente (72,5%) (4,5). En cuanto a la edad de presentación, estudios mencionan 31 años promedio, con una prevalencia mayor en el género femenino (3).…”
Section: Introductionunclassified